Download presentation

Presentation is loading. Please wait.

Published byRolando Knighton Modified about 1 year ago

1
2.4 – Solving Equations with the Variable on Each Side

2
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1)

3
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1)

4
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k + 4.5

5
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k + 4.5

6
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k

7
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k

8
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = 4.5

9
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 =

10
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 =

11
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k = -9.5

12
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k =

13
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k =

14
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k = k = 19

15
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k = k = 19 Ex. 2 2(b – 3) = 3(b – 1)

16
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k = k = 19 Ex. 2 2(b – 3) = 3(b – 1) 2(b)–2(3) = 3(b)–3(1) 2b – 6 = 3b – 3 -3b -3b -b – 6 = b = b = -3

Similar presentations

© 2016 SlidePlayer.com Inc.

All rights reserved.

Ads by Google